Planiranje razvojnih rešitev podjetja: strokovna monografija - Štrukelj, Tjaša (2017)
Planning of Development Solutions for the Enterprises: Professional Monograph. In the professional monograph entitled Planning the development solutions of enterprises authors examine the institution of the family and the development of family business on the case of Slovenian enterprise, provide results of affection of Slovenian enterprises for innovations, explain sectorial analysis of credit ratings to help enterprises making decisions on business partners, analysis of the perceived size of the export barriers in time of financial and economic crisis on the case of Slovenian exporters, explore the identification and assessment of new and complex risks, analyse the practical teaching of students and teaching methods of transferable or transversal competences in Slovenia, explain how to develop cultural intelligence of students and represent the perception of the importance of environmental accounting among students of business economics. All of the foregoing represents different viewpoints of the examination, which can be directed towards the appropriate possibilities of enterprise's development.
Keywords: (Family) business; industry; risks; students; export